Beginning ASP.NET - Nagy, Zsolt (Packt Publishing, 2018)
"ASP.NET is a web framework that helps developers create dynamic web applications and services. This course will help attendees build an understanding of the tried-and-true MVC architecture. They will develop an example shopping cart application whilst building the skills required for real-world development projects with ASP.NET."--Resource description page